Voter Education, Electoral Peace, and Environmental Awareness in South-South Nigeria: Findings from a Descriptive Survey - Ayamba, Itojong Anthony; Bassey, Ugo Samuel; Enang, Agnes Ubana; Abue, Regina Elejie; Effefiom Nsa, Sylvester; Awatt, Christiana Efiong; Ekom, Benjamin Emmanuel; Ezor, Kelvin Isaac; Achum, Valentine Tobechukwu; Apie, Kevin Bankong (Asian Journal of Interdisciplinary Research, 2026)
The study examined public perceptions of voter education, democratic participation, electoral peace, and environmental awareness in South-South Nigeria. Grounded in Human Security Theory, the study employed a descriptive cross-sectional survey design to determine whether respondents perceived that voter education promotes peaceful electoral participation and environmentally responsible electoral conduct within a politically volatile and environmentally vulnerable region. Data were collected from August to December 2025 using a structured electronic questionnaire administered through SurveyMonkey with online convenience sampling. A total of 5,000 valid responses were obtained across the six states of South-South Nigeria. Data were analysed using descriptive statistics and the Chi-square (χ²) test of association. The findings showed that 76% of respondents agreed that voter education contributes to citizens’ understanding of electoral processes, while 75% agreed that sustained voter education contributes to peaceful coexistence before, during, and after elections. Regarding environmental awareness, 68% of respondents agreed that integrating environmental messages into voter education helps mitigate harmful electoral practices such as vandalism, pollution, and tyre burning. Inferential analysis further revealed statistically significant associations between perceptions of voter education and democratic participation (χ² = 842.61, p < 0.05), electoral peace (χ² = 916.37, p < 0.05), and environmental awareness (χ² = 684.24, p < 0.05). The study concludes that most respondents in South-South Nigeria view voter education as a vital civic tool that can promote electoral peace, democratic participation, and environmental awareness in a fragile democratic environment. The study recommends sustained voter education campaigns and the incorporation of environmental awareness into civic sensitisation programmes in politically sensitive areas.